Cost-Effectiveness of Elbasvir/Grazoprevir for the Treatment of Chronic Hepatitis C: A Systematic Review - Liu, Jinyu; Guo, Min; Ke, Lei; You, Ruxu (Frontiers in Public Health, 2022)
Objective This study aims to systematically review recent economic evaluations of elbasvir/grazoprevir (EBR/GZR) for chronic hepatitis C (CHC), to critically appraise the reporting quality and to summarize the results. Methods A literature search was undertaken using Medline, Embase, the Cochrane Library, EconLit, China National Knowledge Infrastructure, Wanfang Data, and Chongqing VIP to identify original articles containing economic evaluations of EBR/GZR for CHC published between 1 January 2000 and 31 December 2020. The Consolidated Health Economic Evaluation Reporting Standards statement was used to assess the quality of reporting of the articles. Results Of 93 articles identified, 13 studies fulfilled the inclusion criteria. These studies were conducted in 4 countries, and 8 active interventions were assessed. The target population was patients infected with CHC genotype 1 infection in all studies. Eight out of 13 studies that compared EBR/GZR vs. other direct antiviral agents suggested that EBR/GZR was generally more cost-effective or dominant than daclatasvir/asunaprevir (DCV/ASV), sofosbuvir/velpatasvir (SOF/VEL), ledipasvir/sofosbuvir (LDV/SOF), ombitasvir/paritaprevir/ritonavir + dasabuvir (3D) but not more cost-effective than glecaprevir/pibrentasvir (GLE/PIB). Two studies from China and one study from the USA that compared EBR/GZR vs. pegylated interferon and ribavirin (PegIFN/RBV) consistently indicated that EBR/GZR was generally more cost-effective than PegIFN/RBV. One study from Italy compared EBR/GZR with SOF + PegIFN/RBV and suggested that EBR/GZR had a lower cost and higher effectiveness. One study from France and one study from the USA confirmed that compared with non-therapy for patients with chronic kidney disease, EBR/GZR was cost-effective at commonly accepted current standards. All included studies were of good quality of reporting, with an average score of 21.9 (range 19–23). Conclusion EBR/GZR for CHC genotype 1 might be cost-effective or dominant compared with PegIFN/RBV and other direct antiviral agents (SOF/VEL, 3D, DCV/ASV, LDF/SOF) or non-therapy. However, under certain assumptions, EBR/GZR was not a cost-effective alternative for CHC patients vs. GLE/PIB.